Does Zero Road Toll Create Unliveable Neighbourhoods? - Curtis, Carey; Aulabaugh, B. (2001)
The purpose of this paper is to promote a wider debate about the way forward. Is it possible to achieve the objectives of both a liveable neighbourhood and of zero tolerance for the road toll. To enable this, the paper starts by highlighting the main objectives and approach put forward by those planning for road safety. Then the paper examines the main approach and objectives for new urbanism or liveable neighbourhoods as put forward by the Western Australian government. Using examples the paper examines the approach now being proposed for traffic management under new urbanism principles and highlights the key issues of concern in conventional road safety. It is argued that it is possible to achieve the objectives of both groups, there may however be a need for further empirical research to support the new urbanist traffic management approach. The prime means of achieving this is through greater multi-disciplinary working rather than a polarised debate. Furthermore, it may be that the main physical design concept that both groups should focus on is speed reduction as this can effectively result in the achievement of both groups' objectives. It is concluded that there are limits to the extent to which physical design can achieve zero road toll, changing attitudes and behaviour may ultimately be the most valuable approach.